2013
DOI: 10.1177/1545968313481283
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sleep Patterns Following Traumatic Brain Injury

Abstract: These findings highlight the importance of assessing and addressing pain, anxiety, and depression as part of the process of treating TBI-related sleep disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 46 publications
3
43
1
1
Order By: Relevance
“…The secondary outcomes thus compared TBI patients with controls across subjective measures of sleep. In light of previous findings, 9,11,18,21,24,25 it was hypothesized that when compared to controls, patients with TBI would display increased daytime sleepiness, and score higher across all domains of the PSQI, indicating poorer sleep quality.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The secondary outcomes thus compared TBI patients with controls across subjective measures of sleep. In light of previous findings, 9,11,18,21,24,25 it was hypothesized that when compared to controls, patients with TBI would display increased daytime sleepiness, and score higher across all domains of the PSQI, indicating poorer sleep quality.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Of the 15 authors contacted, 9-12,18-21,24-30 7 replied with the requested objective data, 11,12,19,21,[25][26][27] with 4 supplying subjective data. 9,18,24,29 Two authors were unable to provide data for all measures of interest, 10,20 but these studies were able to be included in some analyses. Two authors were unable to provide objective data and these studies were excluded, 28,30 as the data were inadequately reported.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between sleep disturbances and motor learning has been demonstrated in patients with obstructive sleep apnea, with marked impairment in consolidation (Landry et al, 2014). Sleep quality was not assessed in the current study, although disturbances in sleep quality and architecture (Ponsford et al, 2013) may have contributed to the hypothesized slowed consolidation processes. Several studies investigated sleep after TBI with mixed results.…”
Section: Discussionmentioning
confidence: 64%
“…Pain in relation to the execution of the FOS task, upper extremity or finger movements was not reported by the participants, although an increase in discomfort may have had its effect toward the end of the sessions. Sleep disruptions are common in patients with TBI (Ponsford et al, 2013) and may have contributed to increased motor fatigue during the more intensive 2nd week of training.…”
Section: Discussionmentioning
confidence: 99%